Impact of non-steroidal anti-inflammatory drugs exposure on persistent cough after pulmonary resection in a Chinese tertiary hospital: a prospective cohort study protocol - Rong Zhang; Xin Zhang; Jie Yu; Xuan Yang; Yi-Fan Zhang; Tao He; Bo Men; Zi-Xiong Nian; Xing-Kai Liu; Gong-Hao He; Wen-Ke Cai (BMJ Open, 2025)
Introduction Previous studies have pointed out that persistent cough is a common complication after pulmonary resection and its occurrence is closely related to inflammatory response. However, there are no clinical studies to date that directly verify that the use of non-steroidal anti-inflammatory drugs (NSAIDs) can reduce the incidence of persistent cough after pulmonary resection (CAP). In view of this, this study aimed to explore and confirm whether exposure to NSAIDs can effectively reduce the incidence of CAP through a prospective cohort study.Methods and analysis We will conduct a single-centre, prospective cohort comparative study to investigate the impact of NSAIDs use on persistent cough after video-assisted thoracoscopic (VATS) lung resection surgery. The study will include all patients without preoperative cough symptoms who are scheduled for VATS lung resection. These patients will be divided into exposed and non-exposed groups according to whether they used NSAIDs after surgery. The primary outcome measures of this study are the incidence of CAP and the association between NSAIDs exposure and the incidence of CAP in patients undergoing VATS lung resection, while the secondary outcome parameter was set as severity of cough.Ethics and dissemination This research was approved by the Ethics Committee of the 920th Hospital of the Joint Logistics Support Force of the Chinese People’s Liberation Army (2024-041-01). The study findings will be published in peer-reviewed journals and presented at professional conferences.Trial registration number NCT06476249.